Land Use Identification and Spatial Pattern Suitability Analysis using 2020 Landsat 8 OLI Imagery: Case Study: Cikeruh, Citarik, and Cirasea Sub-watersheds - Rahman, Dwiki Ramadhan; Sandrawati, Apong; Siswanto, Shantosa Yudha (Jurnal Ilmu Tanah dan Lingkungan, 2022)
Cikeruh, Citarik, and Cirasea sub-watersheds are part of the Citarum watershed which has been included in the 15 priority watersheds for critical land restoration. One of the causes of land criticality is land uses that is not in accordance with land capabilities or spatial pattern directions. The purpose of this study was to identify the types of land use in Cikeruh, Citarik, and Cirasea Sub-watersheds in 2020 and to evaluate the suitability of land use based on the spatial pattern of the West Java Regional Spatial Plans period of 2009-2029. This research was conducted through a descriptive-quantitative analysis approach through interpretation of Landsat 8 OLI satellite imagery using supervised classification method and maximum likelihood algorithm. Suitability analysis was conducted using the overlay (union) method between the resulted land use data and the spatial pattern of the West Java Regional Spatial Plans. The results of the Landsat 8 OLI image interpretation identified 5 land uses with the highest area, showed: dry land agriculture, forest, built-up land, rice field, and bare land covered 35,696.60 ha (41.78%), 14,819.90 ha (17.34%), 12,959.50 ha (15.17 %), 9,112.95 ha (10.67%), 5,862.92 (6.86%) respectively. The accuracy level of the classification showed an overall accuracy value of 91.25% and a kappa index reached 0.90. Based on the results of the 2020 land use analysis of the Regional Spatial Plan, it showed that 40,997.18 Ha (47.98%) was suitable, 17,172.46 Ha (20.10%) was not suitable yet, and 2,276.99 Ha (31.92%) ) was not suitable.